2006
DOI: 10.1007/s11547-006-0022-7
|View full text |Cite
|
Sign up to set email alerts
|

Integrated multislice CT and Tc–99m Sestamibi SPECT–CT evaluation of solitary pulmonary nodules

Abstract: Purpose. The purpose of this study was to evaluate efficacy of multislice computed tomography (MSCT) and single photon emission computed tomography (SPECT)-CT with Tc-99m Sestamibi in the assessment of solitary pulmonary nodules of uncertain significance. Scintigraphy was performed using a 'hybrid' g-camera that allows simultaneous acquisition of SPECT and CT images, with interesting results in diagnostic oncology. Materials and methods. Between September 2003 and August2004, 23 patients with a solitary pulmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
1
5
0
1
Order By: Relevance
“…The high NPV of MIBI in the present study is in line with results from the only two previous studies from Turkey and Italy performed in settings with a relatively high prevalence of benign lesions, which resulted in NPVs of 83 and 92%, respectively [15,16]. In the study from Turkey [15], 37 patients (51% benign lesions) were investigated with MIBI and positive scans indicated malignancy with a sensitivity, specificity, PPV and NPV of 79, 83, 79 and 83%, respectively.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The high NPV of MIBI in the present study is in line with results from the only two previous studies from Turkey and Italy performed in settings with a relatively high prevalence of benign lesions, which resulted in NPVs of 83 and 92%, respectively [15,16]. In the study from Turkey [15], 37 patients (51% benign lesions) were investigated with MIBI and positive scans indicated malignancy with a sensitivity, specificity, PPV and NPV of 79, 83, 79 and 83%, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…In the study from Turkey [15], 37 patients (51% benign lesions) were investigated with MIBI and positive scans indicated malignancy with a sensitivity, specificity, PPV and NPV of 79, 83, 79 and 83%, respectively. In the study from Italy [16], 23 SPNs were included, 56% of which were reported to be benign. MIBI positive scans identified all malignant lesions and only one false-positive scan occurred.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the use of msCT in combination with 99m TC sestamibi single photon emission tomography (SPECT-CT) in SPNs has been proposed, with interesting future perspectives in differential diagnosis [10]. Over the last decade, diagnostic imaging of SPNs and staging of lung cancers have rapidly changed with the increasing use of PET scan, which measures the degree of fluorine18-fluorodeoxyglucose ( 18 F-FDG) uptake -or C11-choline [11] -within a lesion.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical Applications of SPECT/CT Cited Anatomical/Disease Site Radiopharmaceutical SPECT/CT Application Adrenal masses 123 I-metaiodobenzylguanidine, 75 Se-cholesterol Anatomical localization [161] Biliary leak 99m Tc-diisopropyl iminodiacetic acid Anatomical localization [141] Bone scintigraphy 99m Tc-methylene diphosphonate, 99m Tc-dicarboxypropane diphosphonate Anatomical localization, attenuation correction [162][163][164][165][166][167][168][169] Brain cancer 99m Tc-tetrofosmin Anatomical localization [170] Breast cancer 99m Tc-sestamibi Anatomical localization [171] Colorectal cancer 99m Tc-labelled macroaggregated albumin Hepatic artery infusion of chemotherapy [172] Coronary artery calcification 99m Tc-tetrofosmin Head/neck cancer L-3-123 I-iodine-alpha-methyl-tyrosine, 123 I-labeled L19(scFv)2 antibody Anatomical localization [175][176][177] Hepatic haemangioma 99m Tc-labelled red blood cells Anatomical localization [178,179] Hepatic carcinoma 99m Tc-macroaggregated albumin Anatomical localization [180] Human immunodeficiency virus (HIV) 99m Tc-sulfur colloid Anatomical localization of microbicide surrogate [138] Infection Gallium-67, 111 In-labeled leukocytes Anatomical localization [133][134][135][136] Left ventricular function 99m Tc-tetrofosmin Regional wall motion evaluation, myocardial muscle mass, ejection fraction, cardiac volumes [118] Lung (ventilation/perfusion) 99m Tc-Technegas, 99m Tc-macroaggregated albumin Anatomical localization and registration of ventilation-perfusion patterns [139,140] Lung cancer 99m Tc-sestamibi, 99m Tc-depreotide Anatomical localization [181][182]…”
mentioning
confidence: 99%